Out-of-focal plane imaging by leakage radiation microscopy. (9th August 2017) - Zhu, Liangfu; Zhang, Douguo; Wang, Ruxue; Wen, Xiaolei; Wang, Pei; Ming, Hai; Badugu, Ramachandram; Lakowicz, Joseph R
Abstract: Leakage radiation microscopy (LRM) is used to investigate the optical properties of surfaces. The front-focal plane (FFP) image with LRM reveals the structural features on the surfaces. A back-focal plane (BFP) image with LRM reveals the angular distribution of the radiation. Herein, we experimentally demonstrate that the out-of-focal plane (OFP) images present a link between the FFP and BFP images and provide optical information that cannot be resolved by either FFP or BFP images. The OFP image provides a link between the spatial location of the emission and the angular distribution from the same location, and thus information about the film's discontinuity, nonuniformity or variable thickness can be uncovered. The use of OFP imaging will extend the scope and applications of the LRM and coupled emission imaging, which are powerful tools in nanophotonics and high throughput fluorescence screening.